Drought Stress-Mediated Transcriptome Profile Reveals NCED as a Key Player Modulating Drought Tolerance in Populus davidiana - Lee, Sang-Uk; Mun, Bong-Gyu; Bae, Eun-Kyung; Kim, Jae-Young; Kim, Hyun-Ho; Shahid, Muhammad; Choi, Young-Im; Hussain, Adil; Yun, Byung-Wook (Frontiers in Plant Science, 2021)
Populus trichocarpa has been studied as a model poplar species through biomolecular approaches and was the first tree species to be genome sequenced. In this study, we employed high throughput RNA-Seq mediated leaf transcriptome analysis to investigate the response of 4 different P. davidiana cultivars to drought stress. Following RNA-Seq, we compared transcriptome profiles and identified two differentially expressed genes (DEGs) with contrasting expression patterns in the drought-sensitive and tolerant groups i.e. up-regulated in the drought-tolerant P. davidiana groups but down-regulated in the sensitive group. Both these genes encode a 9-cis-epoxycarotenoid dioxygenase (NCED), a key enzyme required for abscisic acid (ABA) biosynthesis. HPLC measurements showed a significantly higher ABA accumulation in cultivars of the drought-tolerant group following dehydration. Arabidopsis nced3 loss-of-function mutants showed significantly higher sensitivity to drought stress, ~90% of these plants died after 9 days of drought stress treatment. Real-time PCR analysis of several key genes indicated a strict regulation of drought stress at the transcriptional level in P. davidiana drought-tolerant cultivars. Transgenic P. davidiana NCED3 overexpression (OE) plants were significantly more tolerant to drought stress as compared to the NCED knock-down RNAi lines. Further, the NCED OE plants accumulated a significantly higher quantity of ABA and exhibited strict regulation of drought stress at the transcriptional level. Furthermore, we identified several key differences in the amino acid sequence, predicted structure, and co-factor/ligand binding activity of NCED3 between drought-tolerant and susceptible P. davidiana cultivars. Here we present the first evidence of a significant role of NCED genes in regulating ABA-dependent drought stress responses in the forest tree P. davidiana and uncover the molecular basis of NCED3 evolution associated with increased drought tolerance.